2020
DOI: 10.1097/dss.0000000000002551
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescribing Recommendations After Mohs Micrographic Surgery and Reconstruction: A Delphi Consensus

Abstract: BACKGROUND Prescription opioids play a large role in the opioid epidemic. Even short-term prescriptions provided postoperatively can lead to dependence. OBJECTIVE To provide opioid prescription recommendations after Mohs micrographic surgery (MMS) and reconstruction. METHODS This was a multi-institutional Delphi consensus study consisting of a panel of members of the American College of Mohs Surgery from var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…1 The lack of available evidence limited the scope of the original review to nonsurgical interventions despite the authors' acknowledgment that many guidelines credit surgery as being inexpensive, safe, and effective. 2 A total of 9 studies, encompassing 363 participants, were included for review. There were no trials investigating surgical treatment available for inclusion, and, consequently, the 9 included studies examined only nonsurgical interventions.…”
Section: From the Cochrane Library: Nonsurgical Interventions For Cut...mentioning
confidence: 99%
See 2 more Smart Citations
“…1 The lack of available evidence limited the scope of the original review to nonsurgical interventions despite the authors' acknowledgment that many guidelines credit surgery as being inexpensive, safe, and effective. 2 A total of 9 studies, encompassing 363 participants, were included for review. There were no trials investigating surgical treatment available for inclusion, and, consequently, the 9 included studies examined only nonsurgical interventions.…”
Section: From the Cochrane Library: Nonsurgical Interventions For Cut...mentioning
confidence: 99%
“…2,3 They provide guidance as to which dermatologic procedures necessitate opioids for pain control. In the 2020 guidelines by Donigan et al, 2 a consensus was reached to not routinely prescribe opioids for most complex linear repairs (CLCs) (excluding the nail unit and scalp [2.5 cm) or \20 cm 2 full-thickness skin grafts (FTSG) after Mohs micrographic surgery (MMS). Consensus was not reached for linear closures of [2.5 cm on the scalp or CLC or FTSG of the nail unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with severe pain that is inadequately controlled with acetaminophen and NSAIDs, opioids may be necessary, especially following flap repairs of the scalp, ear, nose, cheek, lip, and perineum 48 . However, opioids are not typically required following dermatologic surgery, and a recent Delphi consensus study using a panel of Mohs surgeons found no scenario for which consensus was met to routinely prescribe opioids following Mohs surgery 49 . Due to the many potential side effects and risk of dependency, opioids should only be prescribed at the lowest efficacious dose and used in combination with nonopioid therapies 50 .…”
Section: Postoperative Pain Managementmentioning
confidence: 99%
“…48 However, opioids are not typically required following dermatologic surgery, and a recent Delphi consensus study using a panel of Mohs surgeons found no scenario for which consensus was met to routinely prescribe opioids following Mohs surgery. 49 Due to the many potential side effects and risk of dependency, opioids should only be prescribed at the lowest efficacious dose and used in combination with nonopioid therapies. 50 When opioids are required following dermatologic procedures, it is typically for less than 36 hours postoperatively.…”
Section: Postoperative Pain Managementmentioning
confidence: 99%